INTRODUCTION OF THE SERINE GREEN FLUORESCENT PROTEIN (sGFP) GENE INTO Pyricularia grisea RACE DC4 ISOLATED FROM Digitaria ciliaris USING Agrobacterium tumefaciens-MEDIATED GENETIC TRANSFORMATION - Stephanie Stephanie; Utut Widyastuti; Suryo Wiyono (BIOTROPIA, 2015)
Blast disease (caused by Pyricularia grisea) has long been known as a serious problem for upland rice, and recently, it has also begun infecting lowland rice. However, the mechanism enabling this range expansion is still unknown. One possible method to study this shift is by inserting a marker gene into P. grisea so that its spread can be monitored. The sGFP (Synthetic Green Fluorescent Protein) gene has been widely used as a reporter to track gene expression and cellular processes in fungi. In this study, the sGFP gene was integrated into the genome of P. grisea isolate DC4 from Digitaria ciliaris. The sGFP plasmid was first introduced into Agrobacterium tumefaciens using the triparental mating method (TPM). Genetic transformation was then carried out by co-cultivating spores of P. grisea DC4 with A. tumefaciens strain LBA4404 harboring the pCAMBIA-sGFP construct. Transformants were selected on medium containing 300 µg/mL hygromycin. Successful integration of the sGFP gene into the fungal genome was confirmed using PCR with sGFP-specific primers, an sGFP–Nos terminator primer pair, and a β-tubulin primer pair as an internal control. Fluorescent microscopy using blue light excitation confirmed sGFP expression in the P. grisea DC4 transformant.